2014
DOI: 10.2147/jbm.s64090
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood banking: from personal donation to international public registries to global bioeconomy

Abstract: The procedures for collecting voluntarily and freely donated umbilical cord blood (UCB) units and processing them for use in transplants are extremely costly, and the capital flows thus generated form part of an increasingly pervasive global bioeconomy. To place the issue in perspective, this article first examines the different types of UCB biobank, the organization of international registries of public UCB biobanks, the optimal size of national inventories, and the possibility of obtaining commercial product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 69 publications
0
51
0
4
Order By: Relevance
“…Although public CBBs supply the overwhelming majority of CBUs that are actually transplanted, private CBBs still play a significant role in the system because they collect, process, and bank more than half of all CBUs in the world. 143 Furthermore, despite having a lower rate of transplantation, the private family banking market depends on and contributes to most of the same infrastructure that public CBBs require. For example, a representative of a private CBB shared about supporting education and outreach programs that also benefit public CBBs.…”
Section: Private(banks((mentioning
confidence: 99%
“…Although public CBBs supply the overwhelming majority of CBUs that are actually transplanted, private CBBs still play a significant role in the system because they collect, process, and bank more than half of all CBUs in the world. 143 Furthermore, despite having a lower rate of transplantation, the private family banking market depends on and contributes to most of the same infrastructure that public CBBs require. For example, a representative of a private CBB shared about supporting education and outreach programs that also benefit public CBBs.…”
Section: Private(banks((mentioning
confidence: 99%
“…64 In Spain, for example, public banks will store UCB for autologous use, but only if it is also available if requested on behalf of an unrelated patient. 65 A survey of potential Swiss donors revealed that 49% would accept a hybrid private/public model. 66 In Australia, recruitment to clinical trials of autologous UCBT has been influenced by differences in policy between public and family banks.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…[4] However, it is imperative to reminder that the donations are made voluntarily. [5,6] Each individual has one chance in a lifetime to save one's own UCB. Accordingly, this requires nurses who are working at the delivery room to collect high-quality UCB units, consequently improving the chances of future lifesaving.…”
Section: Introductionmentioning
confidence: 99%